(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Tokhang is a Visayan word that means to approach and talk. “Oplan tokhang” is the campaign against illegal drugs in the country to improve peace and order. Oplan tokhang involves police visiting the houses of individuals suspected to be involved in illegal drugs to persuade them to stop using drugs and submit themselves to authority for potential rehabilitation. This study aimed to determine the impact of Oplan Tokhang in relation to the Police officer of Valenzuela City. To help them to lessen those problems they encountered and to pursue the campaign against illegal drugs. The findings of this study revealed how the Police officer may assess the impact of Oplan Tokhang in terms of security, psychological, and work status. Security and psychological availability were interpreted as strongly Agreeable. and work status availability was interpreted as disagreeing. The assessment of the respondents on Oplan Tokhang was unsurprisingly blamed for the spate of extrajudicial killings, negative comments on social media, public criticism, and false allegations by the community of the implementation of oplan tokhang. Some of the proposed recommendations are based on the findings of problems encountered in the development and implementation of Oplan Tokhang. The police officer may encourage more community engagement to help bridge any apparent gaps between the police and the community and build a program to help the drug user have a new lifestyle. Philippine National Police should conduct regular seminars to pull them or tug them in the right direction, especially the victims of these illegal drugs, and encourage the parents to voluntarily surrender their children who are hooked on the drugs and undergo the government rehabilitation programs.